Students’ Attitude towards Virtual Learning during Covid-19 in Chitwan - Sharada Khanal (Journal of Balkumari College, 2022)
The COVID-19 pandemic is rapidly accelerating the learning process. As a result, there has been a shift from face- to- face to virtual learning. The major purpose of this research was to identify the interest and attitude of students towards virtual learning during covid-19 pandemic. The study was to determine whether students are interested in virtual learning or not. This survey is based on primary data collected from students who are currently pursuing their degrees. Google form structured questionnaire was distributed via Messenger app to the students of Chitwan district colleges where virtual learning is going on using random sampling method. The result revealed that students are interested in virtual learning. The majority of students found it as an important means of making knowledge widerand bringing social changes despite hindrances (p= 0.001). Virtual learning is a powerful tool for teaching replacing face to face learning in any level as a quick solution to the crisis. However, successful implementation of virtual learning into curriculum requires a well thought-out strategy and equal access of all.